ANALISIS PENDAPATAN USAHATANI DAN PEMASARAN NANAS DI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR - Anisyananda Pauza; Susy Edwina; Eliza Eliza (Universitas Galuh, 2022)
The purpose of this study was to analyze the income of pineapple farming, analyze pineapple marketing, and formulate the potential and constraints in meeting the availability of pineapple throughout the year in Kualu Pineapple Village. This research was conducted by survey method, the sample in this study was taken as much as 25% of the population, so the number of samples taken was 30 farmers. The results of the study showed that the net income received by the sapling farmers was Rp.61.450.970.04/Ha and the tillers were Rp.52.903.030.56/Ha. The value of RCR (Return Cost Ratio) for tiller type farmers is 3.29 and 2.67 tiller stem farmers. This means that the farming carried out equally gains profit because the RCR value obtained is greater than 1 (RCR> 1). The pineapple marketing channel in Kualu Nanas Village consists of 4 channels. The marketing margin for channel I (Rp.4,026.79/Gandeng), channel II (Rp.2,618.75/Gandeng), channel III (Rp.92,051.34/Gandeng), and channel IV is worth 0. The largest share received by farmers is channel IV (100.00%), followed by channel II (70.58%), channel I (60.30%), and channel III (7.95%). An efficient marketing channel is channel IV (3.03%). The number of pineapple agro-industry businesses and the strategic location in marketing pineapples. The obstacle faced by farmers is that there is no written agreement on land that has been planted with pineapples taken before the use rights period.